Teachers' leadership styles and students' academic achievement in english at selected secondary schools in Kuala Lumpur - Hemathy a/p Kunalan (Kulliyyah of Education, International Islamic University Malaysia, 2014)
Education is extremely important for Malaysia to improve its human resources, to help increase economic growth and bring prosperity in a society. This study is conducted to investigate the relationship between teachers' leadership styles and students' academic achievement in English at selected secondary schools in Kuala Lumpur. A quantitative research design is used in this study to address the research problems and the four research questions that are linked to some important gaps identified in the literature. The survey questionnaires were completed by 317 students from three selected secondary schools in Sentul zone, Kuala Lumpur. Data obtained from each of the research instruments was then statistically analysed (descriptive statistics, correlation and ANOVA) using SPSS version 14. Descriptive statistics showed that the English teachers at the three selected national secondary schools exhibited clearly the six leadership styles. ANOVA indicates that there are five significant differences and one insignificant difference between all three national secondary schools with regard to the teachers' practice of leadership styles. The correlation results showed the relationship among the six leadership styles practised by the teachers and the relationship between teachers' leadership styles with students' academic achievement are mostly significant. This study therefore adds a new dimension to the body of literature that will help researchers' efforts to understand the relationship between teachers' leadership styles and students' academic achievement. As this study takes place in the Malaysian context, it contributes to the achievement of effective and successful leaders. The limitations of this study are particularly in scope and site and these are avenues for possible further research.